Presenting a Pathological Model of Obsessive-Compulsive Disorder Based on Maladaptive Perfectionism and Sensitivity to Threat in Nonclinical Population: Mediating Role of Intolerance of Uncertainty - Shahram Vakili heris; Sholeh Livarjani; Naeimeh Moheb (پژوهش‌های کاربردی روانشناختی, 2020)
The purpose of the present study was to investigate the mediating role of Intolerance of Uncertainty (IU) in the relationship between maladaptive perfectionism and Sensitivity to threat with obsessive-compulsive disorder (OCD), using structural equation modeling (SEM). The research design was descriptive-correlation study. The participants were 586 students of Islamic Azad University Tabriz Branch, University of Tabriz and Azarbaijan Shahid Madani University in Iran. They were selected using cluster sampling method. Data were collected by Obsessive Compulsive Inventory Revised (OCI-R), Frost Perfectionism Scale, BIS/BAS scales, and Intolerance of Uncertainty Scale. SEM confirmed the proposed model (χ2 /df = 2.32, RMSEA = 0.05, CFI = 0.95, GFI = 0.94, AGFI = 0.92) and indicated that maladaptive perfectionism and Sensitivity to threat with standardized coefficients of 0.32 and 0.38, respectively, have a significant effect on OCD by the mediation of IU at the P˂0.05 level. The findings, supporting the theoretical model, proposes a suitable framework for psychopathology of the disorder that emphasizes high maladaptive perfectionism and high sensitivity to threat by the mediation of IU due OCD. These findings, can be useful in developing etiology and efficacious therapeutic interventions for OCD.